Formação e função do diretor de escola: análise a partir dos concursos públicos realizados na rede estadual de ensino de São Paulo (1979-2007) - Hojas, Viviani Fernanda [UNESP] (2011)
This research aims to analyze the public notes and the open tests to fill the position of school principal held in state schools in São Paulo between 1979 and 2007, and also the perception that principals have on the function they exercised/exercise in schools. It is considered that the contents of the public notes and open tests, along with the perceptions of principals who carried out the tests, were approved and entered office, may indicate, among other things, the expectations of teaching central organs of São Paulo state concerning the work of this professional and administrative thinking that supposedly guided and/or guides the administration of public schools in the state. By recovering the knowledge trajectory in Administration of Education in Brazil it is observed that the systemic study in this area since its inception, and during a lot of time, was based almost exclusively on General Theory of Administration being marked by the entrepreneurial paradigm. However, under the argument that schools present different objectives from the company, some studies produced in the late 1970s and in the1980s propose the construction of a specific theoretical basis for the school administrative activity. Taking as a grant this theoretical movement in the area, the analysis of different research sources (public notes, tests and interviews with the principals) is centered on the following questions: If there was a path of knowledge in Educational Administration in the country with outstanding characteristics in each period, were these characteristics reflected in the public notes and tests aimed at filling the position of school principal? And in the perception of principals? How? The undertaken analysis allows sketching out some answers in order to assert that, in some way, the theoretical movement was reflected... (Complete abstract click electronic access below)